Problematics Of The Implementation Of Hajj And Umrah (Study Of Law Number 8 Of 2019 Concerning The Implementation Of Hajj And Umrah) - Randi Alfian; Fitri Rafianti (Yayasan Multidimensi Kreatif, 2023)
This research was conducted to find out the implementation of Hajj and Umrah according to Law Number 8 of 2019 concerning the Implementation of Hajj and Umrah and to find out and provide solutions to problems with the implementation of Hajj and Umrah in Indonesia. Hajj is the fifth pillar of Islam that must be performed by every Muslim who is physically, mentally, spiritually, socially, and financially capable and once in a lifetime. The implementation of Hajj is mandated by Law Number 8 of 2019 concerning the Implementation of Hajj and Umrah (PIHU). In accordance with these laws and regulations, the organisation of the Hajj is the responsibility of the government. This is based on the consideration that the implementation of the Hajj is a national duty and involves the dignity and good name of the nation. The implementation of the Hajj in Indonesia as explained in article 2 and article 3 of Law Number 8 of 2019 concerning the Implementation of Hajj and Umrah, that the Implementation of the Hajj is carried out based on the principles of sharia, trust, justice, benefit, benefit, safety, security, professionalism, transparency, and accountability. The normative legal research method is focused on analysing legal documents and applying a library research approach to Law Number 8 of 2019 concerning the Implementation of Hajj and Umrah. Qualitatively analysed data will be presented in the form of systematic descriptions as well, then all data is selected, processed and then stated descriptively so that it can provide solutions to the problems in question. From the overall study that has been presented in accordance with Law No. 8 of 2019 concerning the Implementation of Hajj and Umrah, it can be concluded that the implementation of Hajj and Umrah is inseparable from various problems. From the registration stage, discussion and determination of BPIH, guidance, transportation services, accommodation/lodging services, health, catering and protection of pilgrims, Hajj organisations, Hajj organising committees, and Hajj officers, the main focus of Hajj implementation has been on the provision of accommodation, transportation and catering services. Attention to these service aspects is important to realise the comfort of the pilgrims in performing their hajj, but another thing that must receive attention is the aspect of Hajj guidance, starting from the implementation of Hajj manasik guidance, to Hajj guidance during the implementation of Hajj in Indonesia and Saudi Arabia. It must be said that not all hajj pilgrims have adequate knowledge and competence about hajj, therefore guidance in the implementation of hajj in Saudi Arabia is a necessity that should not be ignored, so that hajj pilgrims can perform their hajj in accordance with the provisions of shari'a and realise independence and resilience in the implementation of hajj and umrah in accordance with Law Number 8 of 2019.